Peroral endoscopic myotomy and fundoplication: a novel NOTES procedure - Inoue, Haruhiro; Ueno, Akiko; Shimamura, Yuto; Manolakis, Anastassios; Sharma, Ashish; Kono, Shin; Nishimoto, Masayuki; Sumi, Kazuya; Ikeda, Haruo; Goda, Kenichi; Onimaru, Manabu; Yamaguchi, Noriko; Itoh, Hiroaki (Endoscopy, 2019)
Background Peroral endoscopic myotomy (POEM) has become the minimally invasive endoscopic treatment for achalasia; however, gastroesophageal reflux (GER) post-POEM has been reported. A pilot study was conducted in which an endoscopic fundoplication was added to the standard POEM (POEM + F) procedure to overcome this issue. We report the technical details of POEM + F and short-term safety results. Methods POEM + F was performed in 21 patients. After completing myotomy, the endoscope was advanced from the submucosal tunnel into the peritoneal cavity. A partial mechanical barrier was created by retracting the anterior gastric wall at the esophagogastric junction with the use of endoclips and an endoloop.Results POEM + F was technically feasible in all cases and created a visually recognizable fundoplication. The clinical course after POEM + F was uneventful. No immediate or delayed complications occurred.Conclusion POEM + F may help mitigate the post-POEM incidence of GER and serve as a minimally invasive endoscopic alternative to a laparoscopic Heller-Dor procedure. This is the largest case series of peroral natural orifice transluminal endoscopic surgery without laparoscopic assistance in the human foregut.